SOSIALISASI MARKETPLACE DALAM UPAYA MENINGKATKAN PENGETAHUAN MASYARAKAT TENTANG PENJUALAN ONLINE DI E-COMMERCE - Mayzal, Tiondon; Noviarita, Heni; Ridwansyah, Ridwansyah (Jurnal Abdimas Bina Bangsa, 2024)
The development of online stores in the marketplace continues to increase. It definitely affects the pattern of transactions between the purchase and the purchase. They don't have to interact in person, samples of goods already have photos and videos. Then the description of the product is available in the description menu of the online store. The purpose of this dedication is that there are many benefits that can be obtained if you have an online store among them, it can reach the market widely, not fill off the rental of the offline store, and then the online store can open for 24 hours, which is more practical and time-saving. With the enforcement of dedication to society related to the socialisation of marketplaces, many communities are interested in creating online stores in the marketplace, especially in the Shopee application